Organic adhesive with antibacterial function as well as preparation method and application thereof
By using cationically modified polysiloxane, combined with guanidine cation groups and microphase separation structure, a medical adhesive with on-demand bonding, on-demand debonding, antibacterial, hemostasis and recyclable functions was developed, which solved the secondary damage and difficulty in recycling of the prior art traditional Chinese medicine adhesive in emergency situations, and achieved efficient and environmentally friendly wound treatment effects.
Patent Information
- Application Number
- CN202411734053.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-29
AI Technical Summary
It is difficult to develop a medical adhesive with on-demand bonding, on-demand debonding, antibacterial, hemostasis and recyclable functions, especially in emergency situations where secondary damage and difficulty in recycling of wounds are caused.
Using cationically modified polysiloxane as the main component, the antibacterial, hemostasis and recovery functions of the adhesive are achieved through the setting of guanidine cation groups and the formation of micro-phase separation structures, and the on-demand bonding and debonding effects of the adhesive are achieved by adjusting the ion molar content and solvent selection.
It achieves rapid and powerful wound hemostasis and antibacterial effects in emergencies, and has gentle debonding properties to avoid secondary damage to the wound, and achieves environmental protection and sustainable use through recycling technology.
Smart Images

Figure CN119529286A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of organic functional molecule synthesis and antibacterial hemostatic medical materials, and specifically relates to an organic adhesive with antibacterial function and a preparation method and application thereof. Background Art
[0002] In the field of antibacterial hemostatic medical adhesives, the statistics of bleeding deaths show that more than 50% of combat casualties are due to bleeding, and 15% to 25% of civilian deaths are due to bleeding. Emergency medical adhesive dressings can effectively close wounds and stop bleeding, especially in environments with limited medical conditions such as the field and battlefield. Medical adhesive dressings can quickly adhere and fix the damaged part of the wound, timely reduce the loss of function of damaged tissues, and win precious time for subsequent treatment. In addition, the market demand for antibacterial hemostatic functions is getting higher and higher.
[0003] In the field of medical on-demand bonding, current commercial adhesives are usually disposable adhesives. Some medical adhesives have low debonding resistance, so it is difficult to achieve tight adhesion underwater; some medical adhesives have high debonding resistance, which will cause secondary damage to the wound during debonding. The market demand for medical adhesives that can be debonded on demand is increasing. It is urgent to develop medical adhesives that can bond and debond on demand.
[0004] For the field of on-demand debonding technology, adhesives that can be debonded on demand are becoming increasingly important in many technical fields. DE19832629A1 describes an adhesive that can be debonded on demand based on thermal energy or radiation energy, WO2010 / 128042A1, WO02 / 46260A1 and WO2010 / 002262A1 describe adhesives that are debonded by heating, US2007 / 0142497A1 describes an adhesive that is debonded by light and heat, and WO2022 / 254267 describes an adhesive that is debonded by electrical stimulation. However, for emergency wound adhesion, the implementation conditions of light response and electrical response are harsh and uncontrollable, and thermal response and force response are prone to cause secondary damage to the wound. Therefore, for on-demand bonding technology, it is urgent to develop a gentle on-demand bonding method to adapt to the use scenarios of medical adhesives.
[0005] In the field of environmentally friendly and recyclable medical adhesive technology, how to develop recyclable medical adhesives is also a difficult point in the field of medical adhesives. CN117402586A describes a highly chemically cross-linked organosilicon adhesive. This type of highly chemically cross-linked material is not soluble and difficult to be recycled in an environmentally friendly manner. In addition, most of the used medical adhesives become medical waste, and it is urgent to develop environmentally friendly and recyclable medical adhesives.
[0006] In summary, there is an urgent need to develop an adhesive that has on-demand bonding, on-demand debonding, antibacterial and hemostatic and recyclable functions. Summary of the invention
[0007] In order to solve the shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide an organic adhesive with antibacterial function, which has on-demand bonding, on-demand debonding, antibacterial and hemostatic and recyclable functions, and can be applied to emergency wound care needs.
[0008] Another object of the present invention is to provide a method for preparing the above-mentioned organic adhesive with antibacterial function.
[0009] Another object of the present invention is to provide application of the above-mentioned organic adhesive having antibacterial function.
[0010] The purpose of the present invention is achieved through the following technical solutions:
[0011] An organic adhesive with antibacterial function, the organic adhesive is a cation-modified polysiloxane having a structure represented by formula (I), (II), (III), (IV) or (V):
[0012]
[0013] Where, X m+ is a guanidine cationic group (guanidine, also known as guanidine, guanidinium, is a group containing a structure in which one C is connected to three N), the guanidine cationic group is arranged at the end group or / and the side chain of the polysiloxane (the above-mentioned cation-modified polysiloxane can be a linear polysiloxane or a cross-linked polysiloxane, and the guanidine cationic group can be specifically arranged at the end group (formula (I)), side chain (formula (II)) of the linear polysiloxane, or at the end group (formula (I)), side chain (formula (II) to (V)) of the cross-linked polysiloxane, or at the side chain (formula (II) to (V)) of the cross-linked polysiloxane, or at the side chain (formula (I)); Y n- It is the anion of guanidine;
[0014] The number of repeating units in formula (II) to formula (V) is 1 to 1000; the repeating unit refers to the part enclosed in brackets; the value range of m and n is 1 to 2;
[0015] R 1 , R 2 and R 3 Can be independently missing groups, or –O–, –S–, –CO–O–, –O–CO–, CO–NR 7 –、–NR 7 –CO–, –O–CO–NR 7 –、–NR 7 –CO–O–or –NR 7 –CO–NR 7–, or an aliphatic, aromatic or fluorinated divalent hydrocarbon group containing 1 to 60 carbon atoms, wherein the hydrocarbon group may be replaced by –O–, –S–, –CO–O–, –O–CO–, CO–NR 7 –、–NR 7 –CO–, –O–CO–NR 7 –、–NR 7 –CO–O–or –NR 7 –CO–NR 7 – intermittent; R 7 represents H or an alkyl group of 1 to 20 carbon atoms, which may be interrupted by a group such as –O–, meaning that both sides of the –O– group are adjacent to carbon atoms;
[0016] R 4 , R 5 and R 6 It can be independently a missing group, or a hydrogen, aliphatic, aromatic or fluorine-containing monovalent hydrocarbon group containing 1 to 60 carbon atoms, and the hydrocarbon group can be -O-, -S-, -CO-O-, -O-CO-, CO-NR 7 –、–NR 7 –CO–, –O–CO–NR 7 –、–NR 7 –CO–O–or –NR 7 –CO–NR 7 – intermittent; R 7 represents H or an alkyl group of 1 to 20 carbon atoms, which may be interrupted by a group such as –O–, meaning that both sides of the –O– group are adjacent to carbon atoms;
[0017] In the formula, the asterisk (*) indicates the connection position with the polysiloxane unit in the polymer (adhesive), and the polysiloxane unit is selected from hydrocarbon siloxane, silicon-functional siloxane, carbon-functional siloxane or inactive modified siloxane; the single line "—" connected to the asterisk indicates a covalent connection, including but not limited to a single bond, a double bond or other chemical bond connection methods, and the other single lines are single bond connections.
[0018] Preferably, the percentage of the monomer units of the guanidine cationic group to the total monomer units is 0.1% to 50%. The "ion molar content" mentioned herein is the percentage of the monomer units containing cations to the total monomer units.
[0019] Preferably, the Y n– It can be a chloride ion (-Cl - ), bromide ion (-Br - ), iodide ion (-I - ), sulfonate (-SO3 – ), sulfate (-OSO3 2- ), carboxylate (-PO32- ), phosphonate (-PO3 2- ) or nitrate ion (-NO3 - )wait.
[0020] Preferably, the hydrocarbon siloxane: that is, the substituents on the silicon atoms are all hydrocarbon groups, mainly including one or more of dimethyl siloxane, diethyl siloxane or methyl phenyl siloxane; the silicon-functional siloxane: that is, the siloxane with functional groups (including Si-X bonds) directly connected to some silicon atoms, mainly including one or more of hydrogen-containing siloxane, hydroxyl siloxane, alkoxy siloxane, acetoxy siloxane, vinyl siloxane, chlorine-terminated siloxane or amino-terminated siloxane; the carbon-functional siloxane: that is, the functional groups ( The siloxane containing Si-RX) mainly includes one or more of aminoalkylsiloxane, epoxyalkylsiloxane, methacryloxyalkylsiloxane, hydroxyalkylsiloxane, sulfidealkylsiloxane, hydroxyalkylsiloxane, chloroalkylsiloxane or cyanoalkylsiloxane; the inactive modified siloxane: that is, siloxane with inactive groups or polymer segments attached to some silicon atoms, mainly includes one or more of polyether siloxane, long-chain alkylsiloxane, long-chain alkoxysiloxane, fluoroalkylsiloxane and siloxane with a main chain containing an alkylene group or a cyclosilazane group.
[0021] Preferably, the cationically modified polysiloxane is a linear polysiloxane or a lightly cross-linked polysiloxane, wherein "lightly cross-linked" means that the cationically modified polysiloxane can still be dissolved or uniformly dispersed in a solvent when it is a three-dimensional cross-linked structure.
[0022] Preferably, the adhesive has a microphase separation structure. Microphase separation is a supramolecular structure. -1 ) at 0.1nm -1 ~5nm -1 The term "supramolecular interaction" used herein refers to hydrogen bonding interactions, electrostatic interactions, donor-acceptor interactions, dipole-dipole interactions, ion pair interactions, van der Waals interactions, hydrophilic interactions and their combinations. The term "microphase separation structure" used herein refers to the aggregation of cationic groups to form nanoscale phase regions that can be detected by the scattering vector q (nm) in X-ray scattering experiments. -1 ) at 0.1nm -1 ~5nm -1 In some embodiments, the adhesive has a microphase separation structure.
[0023] The present invention also provides a composition of an organic adhesive with antibacterial function, which is a copolymer and / or composite material prepared from a cationically modified polysiloxane having a structure shown in formula (I), (II), (III), (IV) or (V). The copolymer refers to a polymer (the adhesive) whose main chain is copolymerized with other types of polymers and combinations thereof in addition to polysiloxane. The composite material refers to a material formed by a physical or chemical composite of a cationically modified polysiloxane and other organic matter, metal, inorganic matter or a mixture thereof. In some embodiments, the adhesive is a cationically modified polysiloxane; in other embodiments, the adhesive is a physical composite material of a cationically modified polysiloxane.
[0024] Another object of the present invention is to provide a method for preparing the above-mentioned organic adhesive having antibacterial function, comprising the following steps:
[0025] (1) stirring an amino-modified polysiloxane, a guanidinating agent and an acid-binding agent at -20°C to 160°C for 0.1 to 120 hours with or without adding a solvent;
[0026] (2) Stop stirring, directly dry the reaction solution or add it to a solvent for precipitation, wash and dry it to obtain a viscous cationic-modified polysiloxane.
[0027] The cation-modified polysiloxane prepared by the present invention is a transparent, difficult-to-flow gel sample after drying. The amino-containing polydimethylsiloxane before the reaction conversion is generally a liquid that flows easily. Therefore, the cationic structure is set in the polysiloxane to greatly increase the viscosity of the material, which is the main design principle for its use as a glue material.
[0028] Preferably, the amino-modified polysiloxane in step (1) contains at least one of an amino terminal group, an amino side group or an amino T-type structure, such as but not limited to a copolymer of (aminopropyl)-methylsiloxane and dimethylsiloxane, an amino-terminated polydimethylsiloxane or a copolymer of (aminopropyl)-methylsiloxane and dimethylsiloxane, a copolymer of (aminoethylaminopropyl)-methylsiloxane and dimethylsiloxane (more preferably an amino-terminated polydimethylsiloxane or a copolymer of (aminopropyl)-methylsiloxane and dimethylsiloxane).
[0029] Preferably, the guanidinating agent in step (1) includes but is not limited to pyrazole-1-carboximide derivatives, preferably 1H-pyrazole-1-carboxamidine hydrochloride.
[0030] Preferably, the acid binding agent in step (1) includes but is not limited to triethylamine and N,N-diisopropylethylamine.
[0031] Preferably, the solvent in step (1) includes at least one polar solvent such as water, methanol, ethanol, acetonitrile, dimethylformamide, dimethyl sulfoxide, etc.
[0032] Preferably, the solvent in step (2) is at least one of acetone, acetonitrile, water, dichloromethane, ether, petroleum ether and the like.
[0033] Preferably, the cationic modified polysiloxane prepared in the above step (2) can be one in which the amino groups are completely converted into guanidine groups or part of the amino groups are converted into guanidine groups. The above sample in which the amino groups are completely converted into guanidine groups can be used directly, and the above sample in which part of the amino groups are converted into guanidine groups can be used after being placed in air at 60°C to 300°C for thermal crosslinking.
[0034] The adhesive and / or its composition of the present invention has the functions of on-demand bonding, on-demand debonding, antibacterial and hemostatic and recyclable, and can be used to prepare medical dressings or medical tissue dry adhesive patches, etc. According to the physical form classification, the adhesive and / or its composition can be prepared into solid products (such as elastomeric products), liquid products (such as solution products or emulsion products), aerosol products (such as spray products) or any mixture thereof. According to the functional classification, the adhesive and / or its composition can be prepared into antibacterial products, antibacterial products, bactericide products, wound closure products, hemostatic products, tissue trauma hemostatic aids, tissue trauma repair products, tissue trauma antibacterial products, pharmaceutical products or surgical products, etc.), which can be applied to emergency wound care needs (such as bandaging, fixation, care, repair and surgery, etc.) to achieve hemostatic and antibacterial effects, and can be debonded on demand during the secondary wound treatment process to protect the wound.
[0035] The present invention provides a medical tissue dry adhesive patch, which is prepared from the above-mentioned organic adhesive with antibacterial function and / or its composition. Specifically, the present invention applies the above-mentioned adhesive and / or its composition between two films with a certain thickness of 0.02mm to 2cm to obtain the medical tissue dry adhesive patch. Preferably, the film can be any type of cloth base, paper base, metal, silicone, polymer film, release film, etc. and their combination. The medical tissue dry adhesive patch is made into a tape or a sticker, and the tape / sticker structure is cut into a desired shape and can be used in medical dressings (including in the preparation of tissue trauma hemostasis aids, tissue wound closure products, tissue trauma repair products and tissue trauma antibacterial products), which is convenient for pasting and debonding as needed.
[0036] The present invention also provides a method for recovering an adhesive, comprising the following steps:
[0037] a. using a solvent to dissolve or disperse the binder; the solvent includes at least one of water, methanol, ethanol, acetonitrile, dimethylformamide, dimethyl sulfoxide and the like polar solvents;
[0038] b. Remove impurities by extraction, centrifugation or precipitation;
[0039] c. Drying to obtain a reusable cationically modified polysiloxane adhesive.
[0040] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0041] 1. The organic adhesive and / or its composition with antibacterial function described in the present invention has the advantage of on-demand bonding. "On-demand bonding" as used herein is defined as: (1) bonding that is sufficient to remain on a dry or wet surface for the required time; (2) bonding at a pressure not exceeding that of the fingertips; usually tacky at room temperature. Bonding surfaces include metals, inorganic substances, polymers, biological epidermis, and biological tissue organs. The organic adhesive and / or its composition with antibacterial function described in the present invention can achieve an adhesion strength of 50 kPa or more to biological tissues. In one embodiment, the adhesive can be bonded to a dry surface. In one embodiment, the adhesive can be bonded to a wet surface. In one embodiment, the adhesive can be bonded to a biological surface.
[0042] 2. The organic adhesive and / or its composition with antibacterial function described in the present invention has the advantage of on-demand debonding. As used herein, "on-demand debonding" is defined as: the adhesive is completely debonded within the required time without peeling or other complex corresponding stimulation, but with the help of mild solvents, and complete debonding means that there is no peel strength or single lap shear strength.
[0043] One of the solutions for implementing on-demand debonding is that the organic adhesive and / or its composition with antibacterial function can achieve rapid debonding assisted by mild solvents, and the mild solvents include polar solvents such as water, methanol, ethanol, acetonitrile, dimethylformamide, dimethyl sulfoxide, or any mixture of these solvents. Corresponding to the medical scenario where the use scenario is urgently needed to debond, the molar content of ions of the adhesive and / or its composition for on-demand debonding is preferably 1% to 50%, and the mild solvent for on-demand debonding is preferably a mixture of ethanol and water, including medical alcohol. In some embodiments, adhesives and / or their compositions with an ion molar content of 2.8% to 22.1% can be quickly debonded in methanol, dimethylformamide, ethanol and medical alcohol. In some embodiments, adhesives and / or compositions thereof with an ion molar content of 22.1% can be rapidly debonded in water or in an ethanol aqueous solution with an ethanol volume fraction ≥ 0%, adhesives and / or compositions thereof with ion molar contents of 6.5%, 8.4% and 8.4% can be rapidly debonded in an ethanol aqueous solution with an ethanol volume fraction ≥ 20%, and adhesives and / or compositions thereof with ion molar contents of 2.8% and 3.8 can be rapidly debonded in an ethanol aqueous solution with an ethanol volume fraction ≥ 40%.
[0044] The second solution for realizing debonding on demand is self-debonding in a mild solvent. The above-mentioned organic adhesive and / or its composition with antibacterial function can be gradually dissolved or dispersed by a mild solvent, and debonding on demand can be achieved according to the required time. Gradually dissolved or dispersed by the liquid of a mild solvent within the required time, spontaneous debonding on demand is achieved. Corresponding to the use scenario of spontaneous debonding inside the human body, the solvent is preferably water or a blood and body fluid environment. In one embodiment, a cation-modified polysiloxane with a molar content of 8.1% ions can self-debond after 10 days underwater. In one embodiment, a cation-modified polysiloxane with a molar content of 22.1% ions can self-debond after 30 minutes underwater.
[0045] 3. The organic adhesive and / or its composition with antibacterial function described in the present invention has the advantages of antibacterial and hemostatic, and can be used for medical tissue adhesive. The medical tissue dry adhesive patch provided by the present invention can be used for rapid hemostasis of tissue trauma, wound tissue healing and repair, and wound antibacterial in a moist physiological environment.
[0046] 4. The organic adhesive and / or its composition with antibacterial function described in the present invention has the advantage of being recyclable. The contaminated adhesive after the biological epidermis is adhered is dissolved or dispersed with the aid of a mild solvent, and the impurities can be easily removed by one or a combination of extraction, centrifugation and precipitation operations, and the solvent can be dried to achieve environmentally friendly recycling. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 The single lap shear strength test results of the adhesive prepared in Example 17 on different substrates under dry conditions;
[0048] Figure 2 The single lap shear strength test results of the adhesive prepared in Example 18 on different substrates under dry conditions;
[0049] Figure 3 The test results of the single lap shear strength of the adhesive prepared in Example 17 on stainless steel under wet conditions over time;
[0050] Figure 4 Schematic diagram of on-demand debonding of the adhesive prepared in Example 17 after 10 days under wet conditions;
[0051] Figure 5 The test results of the single lap shear strength of the adhesive prepared in Example 18 on stainless steel under wet conditions over time;
[0052] Figure 6 Schematic diagram of on-demand debonding of the adhesive prepared in Example 18 after 30 minutes under wet conditions;
[0053] Figure 7 This is a photo showing the effect of the adhesive prepared in Example 17 being wiped on a glass surface with medical alcohol and leaving no adhesive residue;
[0054] Figure 8 This is a schematic diagram of the adhesive prepared in Example 17 being quickly debonded under the action of medical alcohol;
[0055] Fig. 9 The single lap shear strength test results and adhesion effect photos of the adhesive prepared in Example 17 under complex wetting conditions of biological epidermis;
[0056] Fig.10 This is a graph of the diameter of the antibacterial inhibition zone of the adhesive prepared in Example 17 against Staphylococcus aureus;
[0057] Fig.11 This is a photograph of the experimental results of the hemostatic effect of the adhesive prepared in Example 17 on the wound of the mouse short tail;
[0058] Fig.12 This is a photograph of the experimental results of the hemostatic effect of the adhesive prepared in Example 17 on mouse liver wounds;
[0059] Fig.13 This is a photo of the recycling process of the adhesive prepared in Example 17. DETAILED DESCRIPTION
[0060] To illustrate the present invention, the following examples are provided. These examples are for illustrative purposes only and are not intended to limit the scope of the appended claims. In the examples, the structures of the products and intermediates are confirmed by Fourier transform infrared spectroscopy and proton nuclear magnetic resonance spectroscopy. In the examples, the specific materials, dosages, conditions and other details listed should not be construed as improper limitations of the present invention. The embodiments can be realized by appropriately improving the process parameters, but all similar substitutions and modifications are obvious to those skilled in the art, and they are all considered to be included in the present invention. The present invention has been described by preferred embodiments, and relevant personnel can obviously change or appropriately change and combine the methods and applications herein without departing from the content, spirit and scope of the present invention to realize and apply the technology of the present invention.
[0061] Embodiment 1:
[0062] Add amino-containing polydimethylsiloxane (average molecular weight of about 850-900 g / mol, average number of repeating units of dimethylsiloxane m of about 8-9, 5.00 g, 5.56 mmol, 11.45 mmol-NH2), 1H-pyrazole-1-carboxamidine hydrochloride (1.68 g, 11.45 mmol) and N,N-diisopropylethylamine (1.48 g, 11.45 mmol) into a single-mouth bottle, and then add 5 mL of methanol as a reaction solvent. That is, the molar number of amino groups in polydimethylsiloxane, the reaction equivalents of 1H-pyrazole-1-carboxamidine hydrochloride and N,N-diisopropylethylamine are controlled to be 1:1:1, and the solvent is methanol. Stir the mixture at room temperature 25°C for 30 minutes. After stopping stirring, add the reaction solution to 30 mL of acetonitrile for precipitation to obtain a viscous substance, i.e., an adhesive. The viscous material was washed three times with acetonitrile and dried to obtain a transparent gel-like sample that was difficult to flow, while the amino-containing polydimethylsiloxane was a liquid that flowed very easily, proving that the supramolecular structure of the guanidine cation increased the viscosity of the material. The yield of the adhesive was 78%.
[0063] The structural formula of the adhesive is:
[0064] 1 H NMR(ppm,500MHz,Methanol-d4):3.17(t,J=7.1Hz,-NH-CH2-CH2-CH2-Si,2H),1.68–1.58(m,-N H-CH2-CH2-CH2-Si,2H),0.66–0.58(m,-NH-CH2-CH2-CH2-Si,2H),0.16–0.04(m,Si-CH3,44H).
[0065] IR(cm -1 ):2900,3350,3150,2960,1660,1260,1090-1020,800.
[0066] 1 H NMR and IR results showed that the amino groups were completely converted into guanidine cations with a molar content of 22.1%.
[0067] Embodiment 2:
[0068] Add amino-containing polydimethylsiloxane (average molecular weight of about 850-900 g / mol, average number of repeating units of dimethylsiloxane m of about 8-9, 5.00 g, 5.56 mmol, 11.45 mmol-NH2), 1H-pyrazole-1-carboxamidine hydrochloride (3.36 g, 22.91 mmol) and N,N-diisopropylethylamine (4.44 g, 34.36 mmol) into a single-mouth bottle, and then add 5 mL of methanol as a reaction solvent. That is, the molar number of amino groups in polydimethylsiloxane, the reaction equivalents of 1H-pyrazole-1-carboxamidine hydrochloride and N,N-diisopropylethylamine are controlled to be 1:2:3, and the solvent is methanol. Stir the mixture at room temperature 25°C for 30 minutes. After stopping stirring, add the reaction solution to 30 mL of acetonitrile for precipitation to obtain a viscous substance, i.e., an adhesive. The viscous material was washed three times with acetonitrile and dried to obtain a transparent gel-like sample that was difficult to flow, while the amino-containing polydimethylsiloxane was a liquid that flowed very easily, proving that the supramolecular structure of the guanidine cation increased the viscosity of the material. The yield of the adhesive was 82%.
[0069] The structural formula of the adhesive is:
[0070] 1 H NMR(ppm,500MHz,Methanol-d4):3.17(t,J=7.1Hz,-NH-CH2-CH2-CH2-Si,2H),1.68–1.58(m,-N H-CH2-CH2-CH2-Si,2H),0.66–0.58(m,-NH-CH2-CH2-CH2-Si,2H),0.16–0.04(m,Si-CH3,44H).
[0071] IR(cm -1 ):2900,3350,3150,2960,1660,1260,1090-1020,800.
[0072] 1 H NMR and IR results showed that the amino groups were completely converted into guanidine cations with a molar content of 22.1%.
[0073] Embodiment 3:
[0074] Add amino-containing polydimethylsiloxane (average molecular weight of about 850-900 g / mol, average number of repeating units of dimethylsiloxane m of about 8-9, 5.00 g, 5.56 mmol, 11.45 mmol-NH2), 1H-pyrazole-1-carboxamidine hydrochloride (3.36 g, 22.91 mmol) and N,N-diisopropylethylamine (4.44 g, 34.36 mmol) into a single-mouth bottle, and then add 5 mL of methanol as a reaction solvent. That is, the molar number of amino groups in polydimethylsiloxane, the reaction equivalents of 1H-pyrazole-1-carboxamidine hydrochloride and N,N-diisopropylethylamine are controlled to be 1:2:3, and the solvent is methanol. Stir the mixture at 60°C for 5 minutes. After stopping stirring, add the reaction solution to 30 mL of acetonitrile for precipitation to obtain a viscous substance, i.e., an adhesive. The viscous material was washed three times with acetonitrile and dried to obtain a transparent gel-like sample that was difficult to flow, while the amino-containing polydimethylsiloxane was a liquid that flowed very easily, proving that the supramolecular structure of the guanidine cation increased the viscosity of the material. The yield of the adhesive was 85%.
[0075] The structural formula of the adhesive is:
[0076] 1 H NMR(ppm,500MHz,Methanol-d4):3.17(t,J=7.1Hz,-NH-CH2-CH2-CH2-Si,2H),1.68–1.58(m,-N H-CH2-CH2-CH2-Si,2H),0.66–0.58(m,-NH-CH2-CH2-CH2-Si,2H),0.16–0.04(m,Si-CH3,44H).
[0077] IR(cm -1 ):2900,3350,3150,2960,1660,1260,1090-1020,800.
[0078] 1 H NMR and IR results showed that the amino groups were completely converted into guanidine cations with a molar content of 22.1%.
[0079] Embodiment 4:
[0080] Add amino-containing polydimethylsiloxane (average molecular weight of about 850-900 g / mol, average number of repeating units of dimethylsiloxane m of about 8-9, 5.00 g, 5.56 mmol, 11.45 mmol-NH2), 1H-pyrazole-1-carboxamidine hydrochloride (3.36 g, 22.91 mmol) and N,N-diisopropylethylamine (4.44 g, 34.36 mmol) into a single-mouth bottle, and then add 5 mL of ethanol as a reaction solvent. That is, the molar number of amino groups in polydimethylsiloxane, the reaction equivalents of 1H-pyrazole-1-carboxamidine hydrochloride and N,N-diisopropylethylamine are controlled to be 1:2:3, and the solvent is ethanol. Stir the mixture at room temperature 25°C for 5 minutes. After stopping stirring, add the reaction solution to 30 mL of acetonitrile for precipitation to obtain a viscous substance, i.e., an adhesive. The viscous material was washed three times with acetonitrile and dried to obtain a transparent gel-like sample that was difficult to flow, while the amino-containing polydimethylsiloxane was a liquid that flowed very easily, proving that the supramolecular structure of the guanidine cation increased the viscosity of the material. The yield of the adhesive was 83%.
[0081] The structural formula of the adhesive is:
[0082] 1 H NMR(ppm,500MHz,Methanol-d4):3.17(t,J=7.1Hz,-NH-CH2-CH2-CH2-Si,2H),1.68–1.58(m,-N H-CH2-CH2-CH2-Si,2H),0.66–0.58(m,-NH-CH2-CH2-CH2-Si,2H),0.16–0.04(m,Si-CH3,44H).
[0083] IR(cm -1 ):2900,3350,3150,2960,1660,1260,1090-1020,800.
[0084] 1 H NMR and IR results showed that the amino groups were completely converted into guanidine cations with a molar content of 22.1%.
[0085] Embodiment 5:
[0086] Add amino-containing polydimethylsiloxane (average molecular weight of about 850-900 g / mol, average number of repeating units of dimethylsiloxane m of about 8-9, 5.00 g, 5.56 mmol, 11.45 mmol-NH2), 1H-pyrazole-1-carboxamidine hydrochloride (3.36 g, 22.91 mmol) and N,N-diisopropylethylamine (4.44 g, 34.36 mmol) into a single-mouth bottle, and then add 5 mL of ethanol as a reaction solvent. That is, the molar number of amino groups in polydimethylsiloxane, the reaction equivalents of 1H-pyrazole-1-carboxamidine hydrochloride and N,N-diisopropylethylamine are controlled to be 1:2:3, and the solvent is ethanol. Stir the mixture at 78°C for 5 minutes. After stopping stirring, add the reaction solution to 30 mL of acetonitrile for precipitation to obtain a viscous substance, i.e., an adhesive. The viscous material was washed three times with acetonitrile and dried to obtain a transparent gel-like sample that was difficult to flow, while the amino-containing polydimethylsiloxane was a liquid that flowed very easily, proving that the supramolecular structure of the guanidine cation increased the viscosity of the material. The yield of the adhesive was 88%.
[0087] The structural formula of the adhesive is:
[0088] 1 H NMR(ppm,500MHz,Methanol-d4):3.17(t,J=7.1Hz,-NH-CH2-CH2-CH2-Si,2H),1.68–1.58(m,-N H-CH2-CH2-CH2-Si,2H),0.66–0.58(m,-NH-CH2-CH2-CH2-Si,2H),0.16–0.04(m,Si-CH3,44H).
[0089] IR(cm -1 ):2900,3350,3150,2960,1660,1260,1090-1020,800.
[0090] 1 H NMR and IR results showed that the amino groups were completely converted into guanidine cations with a molar content of 22.1%.
[0091] Embodiment 6:
[0092] Add amino-containing polydimethylsiloxane (average molecular weight of about 850-900 g / mol, average number of repeating units of dimethylsiloxane m of about 8-9, 5.00 g, 5.56 mmol, 11.45 mmol-NH2), 1H-pyrazole-1-carboxamidine hydrochloride (3.36 g, 22.91 mmol) and triethylamine (3.48 g, 34.36 mmol) into a single-mouth bottle, and then add 5 mL of ethanol as a reaction solvent. That is, the molar number of amino groups in polydimethylsiloxane, the reaction equivalents of 1H-pyrazole-1-carboxamidine hydrochloride and triethylamine are controlled to be 1:2:3, and the solvent is ethanol. Stir the mixture at 25°C for 30 minutes. After stopping stirring, add the reaction solution to 30 mL of acetonitrile for precipitation to obtain a viscous substance, i.e., an adhesive. The viscous material was washed three times with acetonitrile and dried to obtain a transparent gel-like sample that was difficult to flow, while the amino-containing polydimethylsiloxane was a liquid that flowed very easily, proving that the supramolecular structure of the guanidine cation increased the viscosity of the material. The yield of the adhesive was 86%.
[0093] The structural formula of the adhesive is:
[0094] 1 H NMR(ppm,500MHz,Methanol-d4):3.17(t,J=7.1Hz,-NH-CH2-CH2-CH2-Si,2H),1.68–1.58(m,-N H-CH2-CH2-CH2-Si,2H),0.66–0.58(m,-NH-CH2-CH2-CH2-Si,2H),0.16–0.04(m,Si-CH3,44H).
[0095] IR(cm -1 ):2900,3350,3150,2960,1660,1260,1090-1020,800.
[0096] 1 H NMR and IR results showed that the amino groups were completely converted into guanidine cations with a molar content of 22.1%.
[0097] Embodiment 7:
[0098] Add amino-containing polydimethylsiloxane (average molecular weight of about 5000 g / mol, average number of repeating units of dimethylsiloxane m of about 64, 5.00 g, 1.0 mmol, 1.84 mmol-NH2), 1H-pyrazole-1-carboxamidine hydrochloride (0.54 g, 3.68 mmol) and N,N-diisopropylethylamine (0.71 g, 5.52 mmol) into a single-mouth bottle, and then add 5 mL of methanol as a reaction solvent. That is, the molar number of amino groups in polydimethylsiloxane, the reaction equivalents of 1H-pyrazole-1-carboxamidine hydrochloride and N,N-diisopropylethylamine are controlled to be 1:2:3, and the solvent is methanol. Stir the mixture at room temperature 25°C for 30 minutes. After stopping stirring, add the reaction solution to 30 mL of acetonitrile for precipitation to obtain a viscous substance, i.e., an adhesive. The viscous material was washed three times with acetonitrile and dried to obtain a transparent gel-like sample that was difficult to flow, while the amino-containing polydimethylsiloxane was a liquid that flowed very easily, proving that the supramolecular structure of the guanidine cation increased the viscosity of the material. The yield of the adhesive was 91%.
[0099] The structural formula of the adhesive is:
[0100] 1 H NMR(ppm,500MHz,Methanol-d4):3.16(t,J=7.1Hz,-NH-CH2-CH2-CH2-Si,2H),1.70–1.56(m,-NH -CH2-CH2-CH2-Si,2H),0.69–0.54(m,-NH-CH2-CH2-CH2-Si,2H),0.25–-0.04(m,Si-CH3,279H).
[0101] IR(cm -1 ):2900,3350,3150,2960,1660,1260,1090-1020,800.
[0102] 1 H NMR and IR results showed that the amino groups had been completely converted into guanidine cations with a molar content of 2.8%.
[0103] Embodiment 8:
[0104] Add amino-containing polydimethylsiloxane (average molecular weight of about 8000 g / mol, average number of repeating units of dimethylsiloxane m of about 110-111, average number of repeating units of guanidine-containing siloxane n of about 4-6, 5.00 g, 0.63 mmol, 2.48 mmol-NH2), 1H-pyrazole-1-carboxamidine hydrochloride (0.36 g, 2.48 mmol) and N,N-diisopropylethylamine (0.32 g, 2.48 mmol) into a single-mouth bottle, and then add 5 mL of methanol as a reaction solvent. That is, the molar number of amino groups in polydimethylsiloxane, the reaction equivalents of 1H-pyrazole-1-carboxamidine hydrochloride and N,N-diisopropylethylamine are controlled to be 1:1:1, and the solvent is methanol. Stir the mixture at room temperature 25°C for 30 minutes. After stopping stirring, add the reaction solution to 30 mL of acetonitrile for precipitation to obtain a viscous substance, i.e., an adhesive. The viscous material was washed three times with acetonitrile and dried to obtain a transparent gel-like sample that was difficult to flow, while the amino-containing polydimethylsiloxane was a liquid that flowed very easily, proving that the supramolecular structure of the guanidine cation increased the viscosity of the material. The yield of the adhesive was 85%.
[0105] The structural formula of the adhesive is
[0106] 1 H NMR(ppm,500MHz,Methanol-d4):3.19–3.13(m,-NH-CH2-CH2-CH2-Si,2H),1.73–1.56(m,-NH- CH2-CH2-CH2-Si,2H),0.66–0.53(m,-NH-CH2-CH2-CH2-Si,2H),0.23–-0.02(m,Si-CH3,146H).
[0107] IR(cm -1 ):2900,3350,3150,2960,1660,1260,1090-1020,800.
[0108] 1 H NMR and IR results showed that the amino groups had been completely converted into guanidine cations with a molar content of 3.8%.
[0109] Embodiment 9:
[0110] Add amino-containing polydimethylsiloxane (average molecular weight of about 8000 g / mol, average number of repeating units of dimethylsiloxane m of about 110-111, average number of repeating units of guanidine-containing siloxane h of about 4-6, 5.00 g, 0.63 mmol, 2.48 mmol-NH2), 1H-pyrazole-1-carboxamidine hydrochloride (0.18 5, 1.24 mmol) and N,N-diisopropylethylamine (0.96 g, 7.44 mmol) into a single-mouth bottle, and then add 5 mL of methanol as a reaction solvent. That is, the molar number of amino groups in polydimethylsiloxane, the reaction equivalents of 1H-pyrazole-1-carboxamidine hydrochloride and N,N-diisopropylethylamine are controlled to be 1:0.5:3, and the solvent is methanol. Stir the mixture at room temperature 25°C for 30 minutes. After stopping stirring, add the reaction solution into 30 mL of acetonitrile for precipitation to obtain a viscous substance, i.e., an adhesive. The viscous material was washed three times with acetonitrile and dried to obtain a transparent gel-like sample that was difficult to flow, while the amino-containing polydimethylsiloxane was a liquid that flowed very easily, proving that the supramolecular structure of the guanidine cation increased the viscosity of the material. The yield of the adhesive was 88%.
[0111] The structural formula of the adhesive is:
[0112] 1 H NMR(ppm,500MHz,Methanol-d4):3.19–3.13(m,-NH-CH2-CH2-CH2-Si,1H),2.69–2.59(m,NH2-CH2-CH2-CH2,1H),1.73–1.56(m,-NH-CH2-CH2-CH2-Si,1 H),1.50–1.38(m,NH2-CH2-CH2-CH2,1H),0.66–0.53(m,-NH-CH2-CH2-CH2-Si,1H),0.58–0.44(m,NH2-CH2-CH2-CH2,1H),0.23–-0.02(m,Si-CH3,146H).
[0113] IR(cm -1 ):2900,3350,3150,2960,1660,1260,1090-1020,800.
[0114] 1 H NMR and IR results showed that the amino groups had been partially converted into guanidine cations with a molar content of 1.9%.
[0115] Embodiment 10:
[0116] Add amino-containing polydimethylsiloxane (average molecular weight of about 8000 g / mol, average number of repeating units of dimethylsiloxane m of about 110-111, average number of repeating units of guanidine-containing siloxane h of about 4-6, 5.00 g, 0.63 mmol, 2.48 mmol-NH2), 1H-pyrazole-1-carboxamidine hydrochloride (0.29 g, 1.98 mmol) and N,N-diisopropylethylamine (0.96 g, 7.44 mmol) into a single-mouth bottle, and then add 5 mL of methanol as a reaction solvent. That is, the molar number of amino groups in polydimethylsiloxane, the reaction equivalents of 1H-pyrazole-1-carboxamidine hydrochloride and N,N-diisopropylethylamine are controlled to be 1:0.8:3, and the solvent is methanol. Stir the mixture at 60°C for 5 minutes. After stopping stirring, add the reaction solution to 30 mL of acetonitrile for precipitation to obtain a viscous substance, i.e., an adhesive. The viscous material was washed three times with acetonitrile and dried to obtain a transparent gel-like sample that was difficult to flow, while the amino-containing polydimethylsiloxane was a liquid that flowed very easily, proving that the supramolecular structure of the guanidine cation increased the viscosity of the material. The yield of the adhesive was 83%.
[0117] The structural formula of the adhesive is
[0118] 1 H NMR(ppm,500MHz,Methanol-d4):3.19–3.13(m,-NH-CH2-CH2-CH2-Si,4H),2.82–2.50(m,NH2-CH2-CH2-CH2,1H),1.73–1.56(m,-NH-CH2-CH2-CH2-Si,4H ),1.65–1.40(m,2NH2-CH2-CH2-CH2,1H),0.66–0.53(m,-NH-CH2-CH2-CH2-Si,4H),0.63–0.41(m,NH2-CH2-CH2-CH2,1H),0.23–-0.02(m,Si-CH3,365H).
[0119] IR(cm -1 ):2900,3350,3150,2960,1660,1260,1090-1020,800.
[0120] 1 H NMR and IR results showed that the amino groups had been partially converted into guanidine cations with a molar content of 3.0%.
[0121] Embodiment 11:
[0122] The products of Example 9 and Example 10 were placed in air and heated at 300°C for 0.5 hours to cause the residual amino groups to undergo a cross-linking reaction. However, after cross-linking, the products were still soluble or dispersed in methanol or ethanol. The cross-linked samples were still colloid samples that were difficult to flow. The structural formula of the adhesive is
[0123]
[0124] Embodiment 12:
[0125] Add amino-containing polydimethylsiloxane (average molecular weight of about 8000 g / mol, average number of repeating units of dimethylsiloxane m of about 110-111, average number of repeating units of guanidine-containing siloxane n of about 4-6, 5.00 g, 0.63 mmol, 2.48 mmol-NH2), 1H-pyrazole-1-carboxamidine hydrochloride (0.73 g, 4.96 mmol) and N,N-diisopropylethylamine (0.96 g, 7.44 mmol) into a single-mouth bottle, and then add 5 mL of ethanol as a reaction solvent. That is, the molar number of amino groups in polydimethylsiloxane, the reaction equivalents of 1H-pyrazole-1-carboxamidine hydrochloride and N,N-diisopropylethylamine are controlled to be 1:2:3, and the solvent is ethanol. Stir the mixture at room temperature 25°C for 5 minutes. After stopping stirring, add the reaction solution to 30 mL of acetonitrile for precipitation to obtain a viscous substance, i.e., an adhesive. The viscous material was washed three times with acetonitrile and dried to obtain a transparent gel-like sample that was difficult to flow, while the amino-containing polydimethylsiloxane was a liquid that flowed very easily, proving that the supramolecular structure of the guanidine cation increased the viscosity of the material. The yield of the adhesive was 86%.
[0126] 1 H NMR(ppm,500MHz,Methanol-d4):3.19–3.13(m,-NH-CH2-CH2-CH2-Si,2H),1.73–1.56(m,-NH- CH2-CH2-CH2-Si,2H),0.66–0.53(m,-NH-CH2-CH2-CH2-Si,2H),0.23–-0.02(m,Si-CH3,146H).
[0127] IR(cm -1 ):2900,3350,3150,2960,1660,1260,1090-1020,800.
[0128] 1 H NMR and IR results showed that the amino groups were completely converted into guanidine cations with a molar content of 3.8%.
[0129] Embodiment 13:
[0130] Add amino-containing polydimethylsiloxane (average molecular weight of about 8000 g / mol, average number of repeating units of dimethylsiloxane m of about 110-111, average number of repeating units of guanidine-containing siloxane n of about 4-6, 5.00 g, 0.63 mmol, 2.48 mmol-NH2), 1H-pyrazole-1-carboxamidine hydrochloride (0.73 g, 4.96 mmol) and N,N-diisopropylethylamine (0.96 g, 7.44 mmol) into a single-mouth bottle, and then add 5 mL of ethanol as a reaction solvent. That is, the molar number of amino groups in polydimethylsiloxane, the reaction equivalents of 1H-pyrazole-1-carboxamidine hydrochloride and N,N-diisopropylethylamine are controlled to be 1:2:3, and the solvent is ethanol. Stir the mixture at 78°C for 5 minutes. After stopping stirring, add the reaction solution to 30 mL of acetonitrile for precipitation to obtain a viscous substance, i.e., an adhesive. The viscous material was washed three times with acetonitrile and dried to obtain a transparent gel-like sample that was difficult to flow, while the amino-containing polydimethylsiloxane was a liquid that flowed very easily, proving that the supramolecular structure of the guanidine cation increased the viscosity of the material. The yield of the adhesive was 92%.
[0131] The structural formula of the adhesive is
[0132] 1 H NMR(ppm,500MHz,Methanol-d4):3.19–3.13(m,-NH-CH2-CH2-CH2-Si,2H),1.73–1.56(m,-NH- CH2-CH2-CH2-Si,2H),0.66–0.53(m,-NH-CH2-CH2-CH2-Si,2H),0.23–-0.02(m,Si-CH3,146H).
[0133] IR(cm -1 ):2900,3350,3150,2960,1660,1260,1090-1020,800.
[0134] 1 H NMR and IR results showed that the amino groups had been completely converted into guanidine cations with a molar content of 3.8%.
[0135] Embodiment 14:
[0136] Add amino-containing polydimethylsiloxane (average molecular weight of about 8000 g / mol, average number of repeating units of dimethylsiloxane m of about 110-111, average number of repeating units of guanidine-containing siloxane n of about 4-6, 5.00 g, 0.63 mmol, 2.48 mmol-NH2), 1H-pyrazole-1-carboxamidine hydrochloride (0.73 g, 4.96 mmol) and triethylamine (0.75 g, 7.44 mmol) into a single-mouth bottle, and then add 5 mL of ethanol as a reaction solvent. That is, the molar number of amino groups in polydimethylsiloxane, the reaction equivalents of 1H-pyrazole-1-carboxamidine hydrochloride and triethylamine are controlled to be 1:2:3, and the solvent is ethanol. Stir the mixture at 25°C for 30 minutes. After stopping stirring, add the reaction solution to 30 mL of acetonitrile for precipitation to obtain a viscous substance, i.e., an adhesive. The viscous material was washed three times with acetonitrile and dried to obtain a transparent gel-like sample that was difficult to flow, while the amino-containing polydimethylsiloxane was a liquid that flowed very easily, proving that the supramolecular structure of the guanidine cation increased the viscosity of the material. The yield of the adhesive was 91%.
[0137] The structural formula of the adhesive is
[0138] 1 H NMR(ppm,500MHz,Methanol-d4):3.19–3.13(m,-NH-CH2-CH2-CH2-Si,2H),1.73–1.56(m,-NH- CH2-CH2-CH2-Si,2H),0.66–0.53(m,-NH-CH2-CH2-CH2-Si,2H),0.23–-0.02(m,Si-CH3,146H).
[0139] IR(cm -1 ):2900,3350,3150,2960,1660,1260,1090-1020,800.
[0140] 1 H NMR and IR results showed that the amino groups were completely converted into guanidine cations with a molar content of 3.8%.
[0141] Embodiment 15:
[0142] Add amino-containing polydimethylsiloxane (average molecular weight of about 2500 g / mol, average number of repeating units of dimethylsiloxane m of about 21 to 31, average number of repeating units of guanidine-containing siloxane n of about 2 to 4, 5.00 g, 2.0 mmol, 5.06 mmol-NH2), 1H-pyrazole-1-carboxamidine hydrochloride (1.48 g, 10.12 mmol) and N,N-diisopropylethylamine (1.96 g, 15.18 mmol) into a single-mouth bottle, and then add 5 mL of methanol as a reaction solvent. That is, the molar number of amino groups in polydimethylsiloxane, the reaction equivalents of 1H-pyrazole-1-carboxamidine hydrochloride and N,N-diisopropylethylamine are controlled to be 1:2:3, and the solvent is methanol. Stir the mixture at room temperature 25°C for 30 minutes. After stopping stirring, add the reaction solution to 30 mL of acetonitrile for precipitation to obtain a viscous substance, i.e., an adhesive. The viscous material was washed three times with acetonitrile and dried to obtain a transparent gel-like sample that was difficult to flow, while the amino-containing polydimethylsiloxane was a liquid that flowed very easily, proving that the supramolecular structure of the guanidine cation increased the viscosity of the material. The yield of the adhesive was 83%.
[0143] The structural formula of the adhesive is
[0144] 1 H NMR(ppm,500MHz,Methanol-d4):3.17(t,J=7.1Hz,-NH-CH2-CH2-CH2-Si,2H),1.71–1.59(m,-N H-CH2-CH2-CH2-Si,2H),0.64–0.55(m,-NH-CH2-CH2-CH2-Si,2H),0.25–-0.07(m,Si-CH3,54H).
[0145] IR(cm -1 ):2900,3350,3150,2960,1660,1260,1090-1020,800.
[0146] 1 H NMR and IR results showed that the amino groups were completely converted into guanidine cations with a molar content of 8.4%.
[0147] Embodiment 16:
[0148] Add amino-containing polydimethylsiloxane (average molecular weight of about 4500 g / mol, average number of repeating units of dimethylsiloxane m of about 46 to 59, average number of repeating units of guanidine-containing siloxane n of about 3 to 4, 5.00 g, 1.11 mmol, 4.11 mmol-NH2), 1H-pyrazole-1-carboxamidine hydrochloride (1.20 g, 8.22 mmol) and N,N-diisopropylethylamine (1.59 g, 12.32 mmol) into a single-mouth bottle, and then add 5 mL of methanol as a reaction solvent. That is, the molar number of amino groups in polydimethylsiloxane, the reaction equivalents of 1H-pyrazole-1-carboxamidine hydrochloride and N,N-diisopropylethylamine are controlled to be 1:2:3, and the solvent is methanol. Stir the mixture at room temperature 25°C for 30 minutes. After stopping stirring, add the reaction solution to 30 mL of acetonitrile for precipitation to obtain a viscous substance, i.e., an adhesive. The viscous material was washed three times with acetonitrile and dried to obtain a transparent gel-like sample that was difficult to flow, while the amino-containing polydimethylsiloxane was a liquid that flowed very easily, proving that the supramolecular structure of the guanidine cation increased the viscosity of the material. The yield of the adhesive was 86%.
[0149] The structural formula of the adhesive is
[0150] 1 H NMR(ppm,500MHz,Methanol-d4):3.17(t,J=7.1Hz,-NH-CH2-CH2-CH2-Si,2H),1.74–1.55(m,-N H-CH2-CH2-CH2-Si,2H),0.71–0.54(m,-NH-CH2-CH2-CH2-Si,2H),0.33–-0.14(m,Si-CH3,98H).
[0151] IR(cm -1 ):2900,3350,3150,2960,1660,1260,1090-1020,800.
[0152] 1 H NMR and IR results showed that the amino groups were completely converted into guanidine cations with a molar content of 6.5%.
[0153] Embodiment 17:
[0154] Add amino-containing polydimethylsiloxane (average molecular weight of about 500000 g / mol, average number of repeating units of dimethylsiloxane m of about 37-43, average number of repeating units of guanidine-containing siloxane n of about 600-610, 5.00 g, 0.01 mmol, 1.04 mmol-NH2), 1H-pyrazole-1-carboxamidine hydrochloride (1.52 g, 10.39 mmol) and N,N-diisopropylethylamine (2.01 g, 15.58 mmol) into a single-mouth bottle, and then add 5 mL of methanol as a reaction solvent. That is, the molar number of amino groups in polydimethylsiloxane, the reaction equivalents of 1H-pyrazole-1-carboxamidine hydrochloride and N,N-diisopropylethylamine are controlled to be 1:2:3, and the solvent is methanol. Stir the mixture at room temperature 25°C for 30 minutes. After stopping stirring, add the reaction solution to 30 mL of acetonitrile for precipitation to obtain a viscous substance, i.e., an adhesive. The viscous material was washed three times with acetonitrile and dried to obtain a transparent gel-like sample that was difficult to flow, while the amino-containing polydimethylsiloxane was a liquid that flowed very easily, proving that the supramolecular structure of the guanidine cation increased the viscosity of the material. The yield of the adhesive was 86%.
[0155] The structural formula of the adhesive is
[0156] 1 H NMR(ppm,500MHz,Methanol-d4):3.16(t,J=7.1Hz,-NH-CH2-CH2-CH2-Si,2H),1.76–1.56(m,-N H-CH2-CH2-CH2-Si,2H),0.70–0.49(m,-NH-CH2-CH2-CH2-Si,2H),0.30–-0.07(m,Si-CH3,60H).
[0157] IR(cm -1 ):2900,3350,3150,2960,1660,1260,1090-1020,800.
[0158] 1 H NMR and IR results showed that the amino groups were completely converted into guanidine cations with a molar content of 8.1%.
[0159] Embodiment 18:
[0160] Add amino-containing polydimethylsiloxane (average molecular weight of about 200,000 g / mol, average number of repeating units of dimethylsiloxane m of about 41 to 48, average number of repeating units of guanidine-containing siloxane n of about 175 to 191, 5.00 g, 0.025 mmol, 13.11 mmol-NH2), 1H-pyrazole-1-carboxamidine hydrochloride (3.84 g, 26.21 mmol) and N,N-diisopropylethylamine (5.08 g, 39.32 mmol) into a single-mouth bottle, and then add 5 mL of methanol as a reaction solvent. That is, the molar number of amino groups in polydimethylsiloxane, the reaction equivalents of 1H-pyrazole-1-carboxamidine hydrochloride and N,N-diisopropylethylamine are controlled to be 1:2:3, and the solvent is methanol. Stir the mixture at room temperature 25°C for 30 minutes. After stopping stirring, add the reaction solution to 30 mL of acetonitrile for precipitation to obtain a viscous substance, i.e., an adhesive. The viscous material was washed three times with acetonitrile and dried to obtain a transparent gel-like sample with an ion molar content of 22.1%. It was difficult to flow, while the amino-containing polydimethylsiloxane was a very easy-to-flow liquid, proving that the supramolecular structure of the guanidine cation increased the viscosity of the material. The adhesive yield was 86%.
[0161] The structural formula of the adhesive is
[0162] 1 H NMR(ppm,500MHz,Methanol-d4):3.26-3.11(t,J=7.1Hz,-NH-CH2-CH2-CH2-Si,2H),1.76–1.56(m, -NH-CH2-CH2-CH2-Si,2H),0.69–0.51(m,-NH-CH2-CH2-CH2-Si,2H),0.25–-0.07(m,Si-CH3,24H).
[0163] IR(cm -1 ):2900,3350,3150,2960,1660,1260,1090-1020,800.
[0164] 1 H NMR and IR results showed that the amino groups were completely converted into guanidine cations with a molar content of 22.1%.
[0165] Embodiment 19:
[0166] The small-angle X-ray scattering experiments of the polydimethylsiloxane (adhesive) containing guanidine cations prepared in Examples 1 to 18 all prove that the scattering vector q (nm -1 ) at 1nm -1 ~3nm -1There is a scattering peak between the two, and the corresponding scattering vector q (nm -1 ) at 1nm -1 ~3nm -1 There are no scattering peaks between them, proving that ionic hydrogen bonding or electrostatic interactions promote the microphase separation of the supramolecular structure.
[0167] Embodiment 20:
[0168] A certain amount of silica powder was added to the adhesives prepared in Examples 1-18, respectively, and the mixture was mechanically mixed until the mixture was uniform and no obvious particles were observed by naked eye to obtain a composite adhesive. The mass of silica accounted for 5%, 10%, 20%, 30%, 40%, and 50% of the mass of the composite adhesive.
[0169] Embodiment 21:
[0170] A certain mass of clay flake powder was respectively added to the adhesives prepared in Examples 1-18, and the mixture was mechanically mixed until the mixture was uniform and no obvious particles were observed by naked eye to obtain a composite adhesive. In the composite adhesives with different addition amounts, the mass of clay flakes accounted for 5%, 10%, 20%, 30%, 40% and 50% of the mass of the composite adhesive.
[0171] Performance Testing:
[0172] 1. Take 100 mg of the adhesives or their composite adhesives with different ion molar contents prepared in Examples 1-18, 20, and 21 and soak them in 10 mL of different solvents. Stir and observe whether the adhesive can be dissolved or dispersed immediately, indicating that its main cohesive force is disintegrated and debonded. The results are shown in Table 1:
[0173] Table 1 Results of whether adhesives or their composite adhesives with different ion molar contents in Examples 1-18, 20, and 21 can be quickly debonded
[0174]
[0175]
[0176] 2. The adhesives prepared in Examples 17 and 18 were coated between the PET film and the PET release film at a thickness of 0.2 mm, and cut to form a transferable adhesive tape / sticker structure. The tape can be used as a sticking material in medical dressings, which is easy to stick and debond as needed.
[0177] 3. The adhesive prepared in Example 17 was applied in air at a thickness of 0.2 mm between two identical substrates (stainless steel sheet, copper sheet, glass sheet) to prepare a single lap test sample. A universal tensile machine was used to perform a tensile test. The single lap shear strength was obtained by dividing the maximum stress of the tensile curve by the initial butt joint area. The unit is kPa to evaluate the adhesion performance under dry conditions. The test was performed at a constant temperature of 25°C. The results are shown in Figure 2. Figure 1 shown.
[0178] 4. The adhesive prepared in Example 18 was applied in air at a thickness of 0.2 mm between two identical substrates (stainless steel sheet, copper sheet, glass sheet) to prepare a single lap test sample. A universal tensile machine was used to perform a tensile test. The single lap shear strength was obtained by dividing the maximum stress of the tensile curve by the initial butt joint area. The unit is kPa. The adhesion performance under dry conditions was evaluated. The test was performed at a constant temperature of 25°C. The results are shown in Figure 2. Figure 2 shown.
[0179] 5. The adhesive prepared in Example 17 was applied underwater with a thickness of 0.2 mm between two identical substrates (stainless steel sheets) to prepare a single lap test sample. A universal tensile test machine was used to perform a tensile test. The single lap shear strength was obtained by dividing the maximum stress of the tensile curve by the initial butt joint area. The unit is kPa. The test was performed at a constant temperature of 25°C to evaluate the weakening of the adhesion performance under wet conditions over time. The results are as follows: Figure 3 Example 17 represents a type of adhesive with low ion molar content (the percentage of ion-containing monomers in the total monomers is less than 15%), which can achieve self-debonding results underwater for 10 days. Figure 4 The results show that the material has excellent adhesion under wet conditions and can be debonded on demand.
[0180] 6. The adhesive prepared in Example 18 was applied underwater at a thickness of 0.2 mm between two identical substrates (stainless steel sheets) to prepare a single lap test sample. A universal tensile machine was used to perform a tensile test. The single lap shear strength was obtained by dividing the maximum stress of the tensile curve by the initial butt joint area. The unit is kPa. The test was performed at a constant temperature of 25°C to evaluate the weakening of the adhesion performance under wet conditions over time. The results are shown in the figure. Figure 5 Example 18 represents a type of adhesive with a high ion molar content (the percentage of ion-containing monomers in the total monomers is greater than 15%), and the schematic diagram of the self-debonding result after 30 minutes underwater is as follows: Figure 6 The results show that the material has excellent adhesion under wet conditions and can be debonded on demand.
[0181] 7. The transferable adhesive tape / sticker structure prepared by the method described in Performance Test Experiment 2 in Example 17 was pasted onto a glass surface, and medical alcohol was used to quickly remove the adhesive without leaving any adhesive residue. Figure 7 Schematic diagram showing that medical alcohol can quickly remove ion-containing adhesives, as shown in Figure 8 shown.
[0182] 8. The adhesive prepared in Example 17 was applied underwater at a thickness of 0.2 mm between two identical substrates (pigskin and sheepskin) to prepare a single lap test sample. A universal tensile machine was used to perform a tensile test. The single lap shear strength was obtained by dividing the maximum stress of the tensile curve by the initial docking area. The unit is kPa. The adhesion performance in the complex wetting environment of the biological epidermis was evaluated. The single lap shear strength was about 15 to 30 kPa. The adhesion photo is as shown in FIG. Fig. 9 The results show that the material has excellent adhesion under the complex wetting conditions of biological epidermis.
[0183] 9. Staphylococcus aureus (S. aureus) was used as a Gram-positive bacterial model to evaluate the antibacterial ability of the adhesive prepared in Example 17 as a medical adhesive. The inhibition zone experiment was carried out and it showed good antibacterial activity, such as Fig.10 shown.
[0184] 10. The adhesive prepared in Example 17 was used to treat the wound of the mouse short tail with the adhesive patch prepared by the method described in Performance Test Experiment 2. The experimental hemostasis time was 91 seconds, which showed good hemostasis function. Fig.11 Shown is a photograph of the bleeding results of the short-tail experiment.
[0185] 11. The adhesive of Example 17 was used to prepare the adhesive patch according to the method described in Performance Test Experiment 2 to treat the liver wound of mice. The hemostasis time of the liver wound was 62 seconds, which showed good hemostasis function. Fig.12 Shown are photos of the bleeding results of the liver wound experiment.
[0186] 12. The adhesive prepared in Example 17 was repeatedly bonded 10 times with pig skin, and dust impurities were added to simulate the condition of the adhesive contaminated by animal fat, hair and dust. Since the material had no chemical cross-linking or the degree of chemical cross-linking was very low, the contaminated adhesive was placed in methanol and stirred to dissolve, and the lower layer of fat was filtered out by standing and stratification. Solid impurities were removed by filtration at the same time. Fig.13 The results show that the material is still recyclable after use in a polluted environment, which is in line with the concept of environmental protection and sustainability.
Claims
1. An organic adhesive with antibacterial function, characterized in that: The organic binder is a cationic-modified polysiloxane having a structure represented by formula (I), (II), (III), (IV) or (V): Where, X m+ is a guanidine cationic group, which is arranged at the end group or / and the side chain of the polysiloxane; Y n- It is the anion of the guanidine cationic group, and the values of m and n are both in the range of 1 to 2; The number of repeating units in formula (II) to formula (V) is 1 to 1000, and the repeating unit refers to the part enclosed in brackets; R 1 , R 2 and R 3 are independently missing groups, or –O–, –S–, –CO–O–, –O–CO–, CO–NR 7 –、–NR 7 –CO–, –O–CO–NR 7 –、–NR 7 –CO–O– or –NR 7 –CO–NR 7 -, or an aliphatic, aromatic or fluorinated divalent hydrocarbon group containing 1 to 60 carbon atoms; R 7 represents H or an alkyl group of 1 to 20 carbon atoms; R 4 , R 5 and R 6 is independently a missing group, or is hydrogen, an aliphatic, aromatic or fluorine-containing monovalent hydrocarbon group containing 1 to 60 carbon atoms; In the formula, the asterisk indicates the connection position with the polysiloxane unit, and the polysiloxane unit is selected from at least one of hydrocarbon siloxane, silicon-functional siloxane, carbon-functional siloxane or inactive modified siloxane; the single line "—" connected to the asterisk indicates a covalent connection, including a single bond, a double bond or other chemical bond connection methods, and the other single lines are single bonds.
2. The organic binder according to claim 1, characterized in that The percentage of the monomer units of the guanidine cationic group to the total monomer units is 0.1% to 50%.
3. The organic binder according to claim 1, characterized in that The monovalent hydrocarbon group or divalent hydrocarbon group is replaced by –O–, –S–, –CO–O–, –O–CO–, CO–NR 7 –、–NR 7 –CO–, –O–CO–NR 7 –、–NR 7 –CO–O– or –NR 7 –CO–NR 7 – intermittent; R 7 It represents H or an alkyl group having 1 to 20 carbon atoms.
4. The organic binder according to claim 1, characterized in that The Y n– is one or more of chloride, bromide, iodide, sulfonate, sulfate, carboxylate, phosphonate or nitrate; The hydrocarbon siloxane includes one or more of dimethyl siloxane, diethyl siloxane or methyl phenyl siloxane; The silicon-functional siloxane includes one or more of hydrogen-containing siloxane, hydroxy siloxane, alkoxy siloxane, acetoxy siloxane, vinyl siloxane, chlorine-terminated siloxane or amino-terminated siloxane; The carbon functional siloxane includes one or more of aminoalkylsiloxane, epoxyalkylsiloxane, methacryloxyalkylsiloxane, hydroxyalkylsiloxane, thioalkylsiloxane, hydroxyalkylsiloxane, chloroalkylsiloxane or cyanoalkylsiloxane; The non-reactive modified siloxane includes at least one of polyether siloxane, long-chain alkyl siloxane, long-chain alkoxy siloxane, fluorohydrocarbon siloxane and siloxane containing a hydrocarbylene group or a cyclosilazane group in the main chain.
5. The organic binder according to claim 1, characterized in that The organic binder has a microphase separation structure.
6. A composition of an organic adhesive having an antibacterial function, characterized in that: It is a copolymer and / or composite material prepared from the organic binder according to any one of claims 1 to 5.
7. The method for preparing the organic adhesive having antibacterial function according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) stirring an amino-modified polysiloxane, a guanidinating agent and an acid-binding agent at -20°C to 160°C for 0.1 to 120 hours with or without adding a solvent; (2) Stop stirring, directly dry the reaction solution or add it to a solvent for precipitation, wash and dry it to obtain a viscous cationic-modified polysiloxane, which is the adhesive.
8. The preparation method according to claim 7, characterized in that: The amino-modified polysiloxane in step (1) contains at least one of an amino terminal group, an amino side group or an amino T-type structure; The guanidinating agent in step (1) comprises a pyrazole-1-carboximide derivative; The acid binding agent in step (1) comprises at least one of triethylamine and N,N-diisopropylethylamine; The solvent in step (1) comprises at least one of water, methanol, ethanol, acetonitrile, dimethylformamide and dimethyl sulfoxide; The solvent in step (2) is at least one of acetone, acetonitrile, water, dichloromethane, ether and petroleum ether.
9. The preparation method according to claim 7, characterized in that: The amino-modified polysiloxane in step (1) includes at least one of a copolymer of (aminopropyl)-methylsiloxane and dimethylsiloxane, an amino-terminated polydimethylsiloxane, a copolymer of (aminopropyl)-methylsiloxane and dimethylsiloxane, and a copolymer of (aminoethylaminopropyl)-methylsiloxane and dimethylsiloxane; The amino groups in the cationic modified polysiloxane prepared in step (2) are completely converted into guanidine groups or part of the amino groups are converted into guanidine groups; wherein the sample in which the amino groups are completely converted into guanidine groups is used directly, and the sample in which part of the amino groups are converted into guanidine groups is placed in air at 60°C to 300°C for thermal crosslinking before use.
10. Use of the organic adhesive with antibacterial function according to any one of claims 1 to 5 and / or the combination of the organic adhesive with antibacterial function according to claim 6 in the preparation of medical dry adhesive patches or medical dressings.
Citation Information
Patent Citations
Medical high-adhesive-force organic silicon adhesive, preparation method and application
CN117402586A
adhesive system for the formation of reversible adhesive bonds
DE19832629A1
Methods for reducing bond strengths, dental compositions, and the use thereof
US20070142497A1
Novel aerogel multifunctional material and preparation method thereof
CN106928908A
Silane containing guanidyl structure and preparation method of silane
CN107964023A